Integrating poverty alleviation and environmental protection efforts: A socio-ecological perspective on menstrual health management. (December 2022) - Angeli, Federica; Jaiswal, Anand Kumar; Shrivastava, Saumya
Abstract: Apt menstrual health management is crucial to the livelihood of low-income, bottom of the pyramid (BOP) women as well as to environmental conservation. However, knowledge is still scant about the factors underpinning women's preferences towards menstrual products, and whether and how the environmental impact of different solutions matter to women's choices. We address this gap by proposing a socio-ecological perspective to understand whether a product's low environmental impact enhances low-income women's uptake of sanitary napkins, thereby supporting poverty alleviation objectives but also efforts geared towards environmental protection. Results from a discrete-choice experiment involving 164 women (n = 1148) in two Indian slums in Delhi and Ahmedabad show that sanitary products' biodegradability is the most important attribute affecting women's preferences towards menstrual hygiene management solutions, which also significantly interacts with women's socio-economic and socio-cultural characteristics. Our findings highlight the potential for business models to find positive synergies between environmental protection and poverty alleviation goals and to situate solutions within the larger socio-ecological context of receiving communities. Highlights: We use a DCE to study menstrual hygiene management (MHM) choices in two Indian slums. Biodegradability is the most important product attribute affecting women's choices. Women's socio-cultural and socio-economic context affects their MHM preferences. A socio-ecological perspective is crucial to understand MHM low-income settings. MHM solutions should and can integrate poverty alleviation and environmental protection.